Peran Guru Dalam Meningkatkan Kualitas Hafalan Siswa Di Ma'had Menara Islamic School Chachocngsoa Thailand - Hidayat, Syarif; Mavianti, Mavianti (Al-Ulum: Jurnal Pendidikan Islam, 2024)
The aim of this research is to find out the role of teachers in improving the quality of students' memorization of the Al-Qur'an and what are the obstacles and solutions. The method in this research is a field study approach using qualitative research. Carried out at Ma'had Menara Islamic School Chachocngsoa Thailand from August to September 2023. As primary data are teachers, and secondary data are heads of foundations and students, data validity is carried out by source triangulation, data is obtained by in-depth observation and interviews, then data descriptive analysis using Miles and Huberman's theory. The results of this research show that the teacher's role in improving the quality of students' memorization of the Qur'an is carried out with: intention, motivating students, continuous murojaah and talaqqi in front of the teachers. The obstacles are; students' age, students' physical condition, lack of motivation, teacher's physical condition, and students' feelings of laziness. The solution is carried out by; carry out evaluations, provide continuous motivation, and provide extra supervision.